Врахування поточного технічного стану автомобільного двигуна в прийнятті рішень щодо виконання профілактичних та відновлювальних робіт - Сахно, В. П.; Кукурудзяк, Ю. Ю. (НТУ "ХПІ", 2015)
В статті описана методика визначення поточного технічного стану автомобільного двигуна на основі автоматизованого інтелектуально–експлуатаційного моніторингу. Така методика направлена на забезпечення оперативного визначення технічного стану двигуна в процесі експлуатації та допомоги в прийнятті обґрунтованих експлуатаційних рішень щодо виконання профілактичних чи відновлювальних робіт на основі комплексних експлуатаційних показників. Приведена ієрархічна структура та методика ідентифікації типових несправностей двигуна.

The article describes a method of determining the current technical condition of the engine based on automated intellectual and operational monitoring. This technique is aimed at providing an operational definition of a technical condition of the engine during operation and assistance in making informed operational decisions on the implementation of preventive or restorative work. Proposed to classify the fault of the automobile engine through the levels. This allows you to create a hierarchical structure that takes into account that a number of individual faults can be replaced with a single time fault. Each level of the fault corresponds to a certain level of monitoring objects are distributed engine. The General algorithm for the identification of faults, which shows the sequence of automatic actions to create a diagnostic model.
Taking into account the current technical condition of automobile engine in making decisions on the implementation of prevention and rehabilitation works
Keywords: технічна експлуатація; моніторинг; несправність; клас; параметр; technical maintenance; monitoring; technical condition